Empirical Environmental Scholarship - Barbash-Riley, Lydia (2018)
The most important development in legal scholarship over the past quarter century has been the rise of empirical research. Drawing upon the traditions of legal realism and the law and economics movement, a variety of social science techniques have delivered fresh perspectives and punctured false claims. But environmental law has been slow to adopt empirical tools, and our findings indicate that it lags behind other fields. There are several clear benefits from an empirical agenda to explore how to make environmental law more effective. But no previous article has applied the lessons from empirical scholarship in other fields to environmental law. This Article fills that gap by assessing the state of environmental empirical scholarship, evaluating the strengths and weaknesses of published approaches to answering empirical questions, and recommending methods to advance the empirical research agenda. Where environmental law scholarship has employed empiricism, it has done so mostly in the pollution control area. More empirical environmental law research relies on analysis of existing data than on the generation of new data, and experimental treatments are completely absent from our review of the literature. One strength of the empirical work in environmental law is analyzing existing data to determine correlations using regression analysis and statistics. But empirical environmental law scholarship underperforms in offering policy prescriptions. This assessment of the field identifies several methods and sources of data that may prove useful in advancing and sharpening empiricism’s contribution to law reform and implementation